Preparation of the Isak 35 Financial Report at the Muhammadiyah Orphanage Foundation, Sumenep Regency - Yandari, Aprilya Dwi; Faisol, Moh.; Andini, Isnani Yuli (Indonesian Journal of Society Development, 2024)
ISAK 35 establishes a basic character for non-profit entities, namely that their resources come from contributors who do not want results, rewards or business profits. However, Indonesian non-profit organizations currently prefer to focus on program quality rather than the importance of financial management systems. One of the problems often faced by non-profit organizations, especially the Muhammadiyah Orphanage, is a lack of understanding of an effective bookkeeping process. Additionally, nonprofit organizations report their finances less frequently. To ensure that partners' financial reports comply with applicable accounting standards, namely ISAK 35, the service team aims to provide direction for socialization, training and mentoring. Based on these problems, this service has provided a good output where foundations can start implementing financial reporting based on ISAK 35. Apart from that, this service also has a very positive impact on donors where they are able to see financial reports in a transparent and accountable manner. . However, it is also hoped that the continuation of this service will be able to use the accounting system well